Etika Pendidik dan Peserta Didik dalam Perspektif Hadis: Kajian Tematik Nilai-Nilai Tarbawi Rasulullah SAW - Nazih, Nazih Sadatul Kahfi (Tarbawi, 2025)
Ethics in the relationship between educators and learners is an important topic in education, especially from an Islamic perspective, which can shape a conducive learning environment and build character. This article aims to examine the ethics of interaction between educators and learners based on the traditions of the Prophet Muhammad, focusing on the principles of compassion, exemplary, and ease in learning. This research uses a qualitative approach with a literature study method, collecting data from relevant traditions, and analysing them with a text interpretation approach. The results show that the traditions provide concrete guidelines in building harmonious relationships between educators and learners, which can enrich the practice of religious values-based education. The findings contribute to the development of the theory of educational ethics in the Islamic context, as well as provide practical implications for the development of a more ethical and humane education system. This research opens space for further exploration of the application of ethics in Islamic education, and its influence on learners' character development.